ANALASISI DAMPAK KEBERADAAN PEMANCAR JARINGAN INTERNET PADA MASYARAKAT DESA RASAU JAYA SATU - Taufiq, Muhammad; Sikwan, Agus; Hidayah, Riama Al (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research is entitled "Analysis of the Impact of the Existence of the Internet Network on the Village Community of Rasau Jaya Satu". The research method used is a qualitative approach with descriptive methods, while collecting data through interviews, observation, and documentation. The existence of an Internet Network Transmitter has become a daily necessity both in the fields of education, health and other fields, so that with an Internet network transmitter it can make it easier for the community to communicate, access social media, make it easier to get information, make it easier to complete work both in education and health, and others. The results of the study are: (1) The positive impact of the existence of an internet network transmitter on the people of Rasau Jaya Satu Village, namely, it makes it easier for people to communicate long distances, people's needs will be met, development and increase in the economic results of people who sell online, make it easier for people to get information , then many people open businesses by utilizing the internet network. (2) The negative impact of the existence of internet network transmitters on the people of Rasau Jaya Satu Village, namely, people easily get incorrect information from social media, many children and adolescents are affected by online games, internet addiction makes teenagers become lazy and lack of attention to the surrounding community, and many frauds that often occur in society through social media.